2013
DOI: 10.1002/art.38065
|View full text |Cite
|
Sign up to set email alerts
|

Unique Protein Signature of Circulating Microparticles in Systemic Lupus Erythematosus

Abstract: Objective. To characterize the unique qualities of proteins associated with circulating subcellular material in systemic lupus erythematosus (SLE) patients compared with healthy controls and patients with other chronic autoimmune diseases.Methods. Using differential centrifugation and high-sensitivity nano-liquid chromatography tandem mass spectrometry, we systematically profiled proteins of microparticles (MPs) from SLE patients (n ‫؍‬ 12), systemic sclerosis (SSc) patients (n ‫؍‬ 6), and rheumatoid arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 54 publications
4
94
0
Order By: Relevance
“…Epidemiological studies suggest that elevated plasma fibrinogen levels are associated with an increased risk of cardiovascular disorders, such as stroke, ischemic heart disease and other throm- Conversely, Watanabe et al [103] observed that serum levels of L-ficolin in patients with SLE were significantly lower when compared with those in healthy subjects. Our results are in agreement with Østergaard et al [104] because they showed an increase in plasma levels of ficolin-2 in SLE patients compared to healthy subjects.…”
supporting
confidence: 94%
“…Epidemiological studies suggest that elevated plasma fibrinogen levels are associated with an increased risk of cardiovascular disorders, such as stroke, ischemic heart disease and other throm- Conversely, Watanabe et al [103] observed that serum levels of L-ficolin in patients with SLE were significantly lower when compared with those in healthy subjects. Our results are in agreement with Østergaard et al [104] because they showed an increase in plasma levels of ficolin-2 in SLE patients compared to healthy subjects.…”
supporting
confidence: 94%
“…Recent studies analysing the MP proteome support this idea [43]. Accordingly, differential 'MP signature' was found in synovial fluid from RA patients compared with other arthritidies [44].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, endothelial bound nucleosomes and C1q are targets for autoantibodies and lead to activation of complement [52]. Endothelial cells are activated during inflammatory processes and may release microparticles containing chromatin fragments that bind anti-dsDNA antibodies [53,54]. Staining kidney sections of New Zealand black/white F1 (NZB/W F1) mice with antiMeca32 and endoglin (CD105) antibodies revealed that IC deposits in the mesangial matrix contained Meca32 and endoglin (Fig.…”
Section: Tubular Cells and Microcapillary Endothelial Cellsmentioning
confidence: 99%